The effect of Islamic Banking and Macroeconomic Variables on Economic Growth: A comparative study of Pakistan - ATTA-UL-MUSTAFA (International Journal of Islamic Economics and Governance, 2020)
The investigation of influence of macroeconomic variables on economic growth remained hot issue for decades. And nowadays increasing importance of Islamic banking and finance industry in Pakistan and its tremendous role in global financial sector has also called for an examining of contribution of Islamic finance in economic growth of Pakistan. This study also compared result of both variables in order to show whether Islamic banking showing great progress or not. So, in order to investigate impact of Islamic finance and macroeconomic variables on economic growth this study used quarterly data from 2009-16 and applies bound testing cointegration technique made within in “Autoregressive distributed lag model”. The result shows that both variables have an influence on economic growth in short run as well as in long run. By comparison of both variables it is shown that Islamic banking possess great potential of growth. So, government may need to refine its legal and regulatory framework in order to increase its impact on economy up to many folds